ADMINISTRATIVE MANAGEMENT IN THE AMUDARYA DEPARTMENT AND THEIR CLASS NATURE - Abdullaev, Anvar Atamuratovich (SCIENCE and SOCIETY, 2026)
In this article, the socio-political and economic situation of the people of the Amudarya region was extremely difficult. As a result of the October coup of 1917, a decree on the administrative management system of the Soviet power, which was forcibly established in the country, including the Amudarya department, was announced, and legal documents were adopted. We can see that the Council of People’s Commissars, which is considered the central authority in Turkestan, has begun to apply its own and unique forms and methods of governance.